Three approaches to modelling heating and evaporation of monocomponent droplets - Antonov D. V. Dmitry Vladimirovich; Tonini T. Simona; Cossali G. E. Gianpietro Elvio; Qubeissi M. A. Mansour Al; Strizhak P. A. Pavel Alexandrovich; Sazhin S. S. Sergey Stepanovich (2024, 2024)
Title screen